Absorption-desorption process of internal curing water in ultra-high performance concrete (UHPC) incorporating pumice: From relaxation theory to dynamic migration model. (October 2022) - Dong, Enlai; Yu, Rui; Fan, Dingqiang; Chen, Ziao; Ma, Xianwei
Abstract: This study aims to clarify the absorption-desorption process of internal curing water by pumice in ultra-high-performance concrete (UHPC) system based on relaxation theory. More exactly, the dynamic migration process of water from pumice in UHPC and its micro/macro properties are analyzed by 1 H nuclear magnetic resonance, backscattering electron, nanoindentation, etc. The results reveal that the prewetted pumice could delay the water release time for 1 h compared with dry pumice (5.5 h), and can continue to absorb about 14% of free water from the end of the mixing process to the beginning of water release. Notably, the release rate of water from prewetted pumice in UHPC is up to 80%, which is beneficial to the alleviation of internal relative humidity decline rate and thus reduces the autogenous shrinkage of UHPC. In addition, the use of prewetted pumice improves the microstructures of UHPC, where compared with river sand, its transport distance of water entraining reaches at 35 μm–55 μm and its interfacial transition zone (ITZ) structure is also denser. Finally, a relaxation theory-based dynamic model is successfully established, which can be used to illustrate the water migration process and predict migration distance in the UHPC system.